Mangrove Literacy House Library: A Social Inclusion-Based Library in the Environment and Sustainability Sector - Suryadin, Asyraf; Amalia, Runi Alcitra; Kusuma, Arja (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
Libraries are essential in educating people about sustainability and environmental issues, particularly in preserving East Belitung’s mangrove ecosystems. The goal of this study is to determine how the Mangrove Literacy House Library, which the Peat and Mangrove Restoration Agency established in collaboration with the Environmental Council of Muhammadiyah Central Executive, has changed into a library that emphasizes social inclusion in the areas of environment and sustainability, particularly concerning the preservation of mangrove ecosystems. This qualitative descriptive study data is gathered through interviews, observation, and documentation and is then analyzed using Miles and Huberman’s models. The findings of this study demonstrated that the RLM library works in partnership with the Sayang Kampong Farmers Group to increase public awareness of environmental issues and sustainability, particularly concerning the preservation of the mangrove ecosystems of East Belitung. Through this partnership, students learn about the environment and sustainability through reading activities at the RLM Library and hands-on experiences at the Sayang Kampong Farmers Group. Students can even put their knowledge of mangrove ecosystems they have learned about in the RLM Library into practice for the Sayang Kampong Farmers Group, making the RLM Library a library based on social inclusion in the environment and sustainability.